Two salamander species respond differently to timber harvests in a managed New England forest - Angus Mossman; Max R. Lambert; Mark S. Ashton; Jessica Wikle; Marlyse C. Duguid (PeerJ, 2019)
Background Managing forests for timber while protecting wildlife habitat is of increasing concern. Amphibians may be particularly sensitive to forest management practices due to their unique biology; however, it is not clear how different species respond to timber harvest practices—particularly over longer time scales. Methods Here we report on the differential responses of two salamander species—the eastern red-backed salamander (Plethodon cinereus Green) and the eastern newt (Notophthalmus viridescens Rafinesque)—to forest harvesting, by examining communities across a 25-year chronosequence of regenerating shelterwood harvests. Results Populations of both species were lowest immediately after harvest, but increased at substantially different rates. Red-backed salamander populations were highest in 20–25 year-old shelterwoods—significantly higher than in mature, unharvested, control (100–120 year old) stands. Eastern newt populations, however, were greatest in unharvested control stands and still had not recovered to population levels found in mature stands in the 25 years since harvest. Red-backed salamander abundances were strongly tied to stand age as well as abundance of decayed coarse woody debris, suggesting that timber harvests influence some wildlife species by affecting a suite of interacting habitat variables that change over time. In contrast, newt abundances were not directly related to stand age but were more related to downed wood and vegetation characteristics. Our results highlight markedly variable responses by two common salamander species to forest harvesting—species with markedly different life histories and reproductive patterns—and that time since harvest may be useful in predicting abundance.